KONFIGURASI PENDIDIKAN KARAKTER BERPARADIGMA KEBANGSAAN; USAHA MENEGUHKAN IDENTITAS DIRI BANGSA DARI KUNGKUNGAN ARUS GLOBALISASI - Mohamad Tulus (Fak. Tarbiyah UIN Maliki Malang, 2012)
Today’s globalization need to be watched out. Though its presence brought many changes to the aspect of technological advancements, we have to anticipate the excesses caused. Due to the presence of globalization and the resulting excesses, the behavior of the Indonesian change following the Western culture (Westernization) which adheres to liberalism. This thing is feared to be able to shift the values ​​of the locality which for centuries became characteristics of the Indonesian in having a character of heroic, nationalism, courtesy and hospitality in accordance with the norms of oriental. Based on the above phenomenon, we need to formulate and promote a character education nation paradigm in order to strengthen the identity of Indonesia. Locality-values ​​that can be included in the character building of having nationalism is the ideas of Ki Hajar Dewantara that are the